MANAJEMEN STRATEGI PELAYANAN INVESTASI : (Studi Kasus Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu (DPMPTSP) Kabupaten Gresik) - Rizky Darmawan (Jurnal Administrasi Publik, 2023)
Abstract: This research was conducted to answer the challenges and problems of investment licensing services in public organizations such as community satisfaction and integrated licensing services in the face of uncertainty, globalization and technological developments in order to improve the quality of special services for administrative services in the investment sector. sector. sector with strategic management. This study uses a qualitative descriptive type with a focus on using the stages of Stephen p. Robbin 2010 such as: strategic planning, strategy implementation and strategy evaluation as well as supporting and inhibiting factors. Collecting research data through in-depth interviews, direct observation and documentation. The data analysis technique used is Miles Huberman and Saldana 2014. The legal basis is based on Law no. 25 of 2007 concerning Investment which was followed up by the Gresik Regency One-Stop Investment and Integrated Services Service (DPMPTSP) through Regent Regulation Number 49 of 2019 concerning Position, Duties and Functions.